Peningkatan Hasil Belajar Pak Menggunakan Model Project Based Learning (PjBL) Fase C Kelas 5 di SD Negeri 030298 Simallopuk - Dahniar Nadeak (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of 5th-grade students at SD Negeri 030298 Simallopuk in the subject of Catholic Religious Education by applying the Project-Based Learning (PjBL) model. This Classroom Action Research was conducted in two cycles, with each cycle involving planning, implementation, observation, and reflection. The results showed that the application of the PjBL model significantly improved students' learning outcomes. In the first cycle, only 67.57% of students achieved mastery, but after improvements in the second cycle, the mastery rate increased to 78.38%. Additionally, the model enhanced student engagement, creativity, and critical thinking skills. Therefore, PjBL is considered effective in improving students' learning outcomes in Catholic Religious Education.